Tradução e adaptação transcultural do questionário breve de hábitos alimentares e atividade física EMOVE (Eat and Move) para pacientes submetidos a cirurgia bariátrica - LIRA, Lyrian Lorena Freire (2025)
Introduction: Obesity is a condition associated with an inadequate diet, with excess calorie consumption and the onset of a sedentary lifestyle. Among the treatments, bariatric surgery can provide a reduction in calorie intake, but individuals undergoing the procedure may regain weight over time. There is a lack of instruments in the Portuguese language that reliably and sensitively assess adherence to healthy eating and physical activity habits in patients undergoing such intervention and its relationship with long-term weight maintenance or reduction. Objective: To translate and adapt the brief, self-administered Eat Move (EMOVE) questionnaire to assess adherence to healthy eating and physical activity habits. Materials and Method: This is a methodological study of translation and cross-cultural adaptation of the EMOVE questionnaire, carried out at Hospital São Domingos, São Luís, Maranhão, Brazil, between January 2022 and December 2024. The Brazilian version of the EMOVE questionnaire was developed following translation (with two Brazilian translators and fluency in Spanish), back-translation (involving two translators with Spanish as their native language), pre-test evaluation with patients with indication for bariatric surgery, adults, of both sexes. From the data, the percentage of understanding of the questionnaire was estimated. Results: A total of 30 patients were evaluated, with a predominance of women (76.7%), mean age of 35.9 ± 9.1 years. A 99.1% understanding of the final Brazilian version of the questionnaire (EMOVE-BR) was observed. Among those evaluated, 93.3% showed dietary and physical activity habits classified as poor, with a mean score of 20.0 ± 7.0 points on the EMOVE-BR questionnaire. Conclusion: The final Brazilian Portuguese version of the EMOVE Questionnaire showed an adequate level of understanding among participants.